Carbohydrate Content in Packaged Chicken Nuggets: Qualitative And Quantitative Analysis - Syifa Alifia Indriani; Nurul Asfia; Agnes Manongga; Riong Seulina Panjaitan (Indonesian Journal of Pharmaceutical Research, 2022)
Nugget products can be made from beef, chicken, fish, and other ingredients, but chicken nuggets are the most popular in the community. Chicken nuggets are products produced from the marinated, ground, minced, and cooked parts of chicken breast meat with breadcrumbs. Qualitative and quantitative tests of carbohydrates are carried out to determine the presence of carbohydrates present in nuggets. Qualitative tests are based on changes in color or deposits formed, while quantitative tests to determine the carbohydrate levels contained in each test material with DNS method. The results showed qualitative analysis of molisch test carbohydrates on samples of chicken meat nuggets brand "B," which positively contained carbohydrates (glucose), while samples of chicken meat nuggets brands "A" and "C" showed negative results. In the Iodin test, all three nugget samples showed positive results for glycogen. The Benedict test yielded negative results for all three nugget samples, indicating that none of them contained sucrose. The three nugget samples all failed the Barfoed test, indicating that they are all members of the disaccharide group. The Seliwanoff test yielded negative results for all three nugget samples, all of which contained glucose, mannose, or galactose. The Osazon test yielded negative results for all three nugget samples. Carbohydrate quantitative test obtained sample concentration on sample nugget of chicken meat brand "A" 0.49 mg/mL, sample of chicken meat nugget brand "B" 0.48 mg/mL and sample nugget of chicken meat brand "C" 0.56 mg/mL. Carbohydrate qualitative analysis on samples of chicken meat nuggets from brand "B" reveals that they positively contain carbohydrates as well as fructose and glycogen. The "C" brand chicken meat nugget sample has a high concentration for quantitative analysis of carbohydrates, indicating that the sample contains more carbohydrates.